2016
DOI: 10.1016/j.tox.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Detection of phase specificity of in vivo germ cell mutagens in an in vitro germ cell system

Abstract: 22In vivo tests for male reproductive genotoxicity are time consuming, resource-23 intensive and their use should be minimised according to the principles of the 3Rs. 24Accordingly, we investigated the effects in vitro, of a variety of known, phase-specific 25 germ cell mutagens, i.e. pre-meiotic, meiotic, and post-meiotic genotoxins, on rat 26 spermatogenic cell types separated using Staput unit-gravity velocity sedimentation, 27 evaluating DNA damage using the Comet assay. N-ethyl-N-nitrosourea (ENU), N-28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 68 publications
(65 reference statements)
1
15
0
Order By: Relevance
“…For spermatocyte fractions, it was 88–90% and 88–92% for the spermatid fractions. The results also were confirmed by Western blotting for phase‐specific markers exactly as described previously [Habas et al, ].…”
Section: Methodssupporting
confidence: 59%
See 4 more Smart Citations
“…For spermatocyte fractions, it was 88–90% and 88–92% for the spermatid fractions. The results also were confirmed by Western blotting for phase‐specific markers exactly as described previously [Habas et al, ].…”
Section: Methodssupporting
confidence: 59%
“…MMS has also been found to induce a high incidence of dominant lethal mutations in spermatids [Ehling, ]. Our previous study [Habas et al, ], using the Comet assay in rat, also showed that ENU produced a high level of DNA damage in spermatogonia incurring significantly greater DNA damage. Spermatocytes were most sensitive to 6‐MP while spermatids were particularly susceptible to MMS [Habas et al, ].…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations